Impact of fertilization on water resources in karst, example of research field site Sinji Vrh - Barbara ČENČUR CURK (Acta Agriculturae Slovenica, 2014)
A research field site (RFS) was established at Sinji Vrh in the western part of Slovenia in order to study flow and solute (particularly pollutant) transport in fractured and karstified rocks, with a focus on the unsaturated zone. RFS consists of surface set-up and a research tunnel, 15 m below the surface. Agrometeorological station was installed on the RFS. A special construction (1.5 m long segments) for collecting water seeping from the ceiling of the research tunnel was developed. At the research field site Sinji Vrh fertilizer application experiments were performed for estimation of impact of fertilization on water resources. Results of the fertiliser application experiments have shown that a thin autochtonous soil cover on karstic rock is insufficient to retain nitrate and prevent pollution of groundwater.